2007
DOI: 10.2134/jeq2006.0182
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Leaching from Cow Manure Patches on Soil Columns

Abstract: The loss of P in overland flow or leachate from manure patches can impair surface water quality. We studied leaching of P from 10-cm-high lysimeters filled with intact grassland soil or with acid-washed sand. A manure patch was created on two grassland and two sand-filled lysimeters, and an additional two grass lysimeters served as blanks. Lysimeters were leached in the laboratory during 234 d with a diluted salt solution, and column effluent was passed through a 0.45-microm filter, analyzed for pH, dissolved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 31 publications
5
35
1
2
Order By: Relevance
“…Single additions of excreta more than tripled the P Ac and TP w in the 0-2 cm soil layer in 50 days. There were no sings of decreasing P solubility towards the end of the experimental period, which supports the results of Chardon et al (2007), who found manure patches to be a source of P for a long time after deposition. Repeated dung additions may result in very high soil P status, especially in areas where cattle tend to congregate.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Single additions of excreta more than tripled the P Ac and TP w in the 0-2 cm soil layer in 50 days. There were no sings of decreasing P solubility towards the end of the experimental period, which supports the results of Chardon et al (2007), who found manure patches to be a source of P for a long time after deposition. Repeated dung additions may result in very high soil P status, especially in areas where cattle tend to congregate.…”
Section: Discussionsupporting
confidence: 89%
“…The water extractable P in dung is composed largely of inorganic P. However, data published in the literature vary considerably due to the different extraction procedures and sample-to-solution ratios used in dung analyses (He et al 2004, Chardon et al 2007). In the present study, the composition of dung was not analysed in detail, but the smaller increase in MUP w in the dung-treated samples over that of MRP w suggests that the majority of the TP w that ended up in the soil with the dung was in inorganic form.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is because P is predominantly found in inorganic form in the manure, readily available to plants. This may be seen in figure 1, where the greatest available P contents were observed in the first days of soil incubation, which indicates that a large part of the P present in the manure is found in the inorganic form, which is the predominant form of accumulation in soils treated with manure (Chardon et al, 2007;Gatiboni et al, 2008;Ceretta et al, 2010a;Guardini et al, 2012a;Lourenzi et al, 2013). Furthermore, the absence of tilling in the no-tillage system favors P accumulation in the soil surface layers because, in the soil, the P may be adsorbed to the surface of functional groups of reactive particles, normally forming inner sphere complexes (specific adsorption) (Barrow, 1999).…”
Section: Resultsmentioning
confidence: 81%
“…A baixa capacidade de adsorção de P de solos arenosos (Rheinheimer et al, 2003) pode contribuir para esse deslocamento vertical. Em relação às formas químicas de P, a literatura indica tanto o deslocamento em formas inorgânicas (Chardon et al, 2007) quanto orgânicas (Djodjic et al, 2004). Deve-se considerar que a maior parte do P contido no esterco está em formas inorgânicas (P-resina) (Cassol et al, 2001).…”
Section: Resultsunclassified